Studies on the Inhibitory Effects of Eucalyptus (Hybrid) Leaf Extracts on the Germination of Certain Food Crops - Swami Rao, N.; Chandrashekara Reddy, P. (Indian Forester, 1984)
Investigations were carried out to study the effect of Eucalyptus (hybrid) leaf extracts on the germination and other growth parameters of selected dry land food crops. The result revealed that the leaf extracts inhibit germination of crop seeds to a certain extent. Overall growth rate of seedlings was also reduced in all the treatmlnts compared to control. Heavy mortality of the seedlings and reduced vigour under laboratory conditionsi indicated that the accumulation of toxic substances is harmful to the growth of seedlings of crop plants. Reduction in vigour and growth rate in the early stages of growth was observed in the field grown seedlings but their gradual recovery indicated that once the inhibitory substances are leached out from soil the harmful effects are minimised. It may not be possible to grow food crop successfully near Eucalyptus plantation in areas with low rainfall where there always a possibility of accumulation of toxic substances in the soil from the leaf litter.